Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan dan Keberlanjutan Penggunaan pada Pengguna Aplikasi Kesehatan - Cynthia Fransiska; Innocentius Bernarto (JURNAL ADMINISTRASI BISNIS, 2021)
This study aims to examine the relationship between service quality, customer satisfaction, continual usage, and the moderating effect of monetary costs on Halodoc users in Indonesia. This research is included in correlational research. The population of this study was all Halodoc users in Indonesia from April to May 2021, and the sample of this study was 190 Halodoc users from all over Indonesia who filled out a questionnaire via a google form. The sampling method used is convenience sampling that is included in the non-probability sampling. The data were analyzed using partial least square structural equation modeling (PLS-SEM). The results show that service quality has a positive effect on customer satisfaction, service quality has a positive effect on continual usage, customer satisfaction has a positive effect on continual usage, and monetary costs do not moderate the relationship between satisfaction and sustainability of use. Based on the results of the study, it can be concluded that increasing sustainability is positively influenced by service quality and customer satisfaction, increasing service quality can increase customer satisfaction and there is no moderating effect of monetary costs.